2009
DOI: 10.4196/kjpp.2009.13.6.491
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK Participates in Muscle-Specific RING Finger 1-Mediated Atrophy in Cast-Immobilized Rat Gastrocnemius Muscle

Abstract: Skeletal muscle atrophy is a common phenomenon during the prolonged muscle disuse caused by cast immobilization, extended aging states, bed rest, space flight, or other factors. However, the cellular mechanisms of the atrophic process are poorly understood. In this study, we investigated the involvement of mitogen-activated protein kinase (MAPK) in the expression of muscle-specific RING finger 1 (MuRF1) during atrophy of the rat gastrocnemius muscle. Histological analysis revealed that cast immobilization indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(73 citation statements)
references
References 35 publications
4
68
1
Order By: Relevance
“…Some investigators have shown that muscle atrophy is mediated by both the PKB/Akt and SAPK/JNK pathways and that the atrophy-associated induction of atrogin-1 is regulated by the inhibition of PKB/ Akt activation 3,22,24) . Furthermore, it has been reported that upregulation of atrogin-1 and MuRF-1 in atrophied muscles are mediated by p38 MAPK and NF-κb, respectively 16,25,26) . However, the relationship between muscle atrophy and the phosphorylation of ERK1/2, p38 MAPK, SAPK/ JNK, and PKB/Akt has not been clearly determined.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some investigators have shown that muscle atrophy is mediated by both the PKB/Akt and SAPK/JNK pathways and that the atrophy-associated induction of atrogin-1 is regulated by the inhibition of PKB/ Akt activation 3,22,24) . Furthermore, it has been reported that upregulation of atrogin-1 and MuRF-1 in atrophied muscles are mediated by p38 MAPK and NF-κb, respectively 16,25,26) . However, the relationship between muscle atrophy and the phosphorylation of ERK1/2, p38 MAPK, SAPK/ JNK, and PKB/Akt has not been clearly determined.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the atrophy characteristics presented in previous reports on rat skeletal muscles [20][21][22] . Both MuRF-1, which contains a RING-finger domain, and atrogin-1/MAFbx, which contains an F-box domain, are E3 ubiquitin ligases, which are known to initiate ATP-dependent ubiquitinmediated proteolysis and promote skeletal muscle atrophy 16,23,25) . Further, MuRF-1 and atrogin-1/ MAFbx are known to be major factors mediating muscle atrophy in a variety of cells and tissues 22,25) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mitogen-activated protein kinases (MAPKs) are also signaling molecules important for regulating various cellular processes in cells, including proliferation, differentiation, and migration (Kim et al, 2009;Lee et al, 2008a,b). MAPK activation is induced by diverse stimuli, including growth factors, hormones, and cytokines .…”
Section: Introductionmentioning
confidence: 99%